The Legal Politics of Protecting Migrant Workers’ Human Rights: Policy Reorientation through the Revision of Law Number 18 of 2017 - Maizidah Salas; Susilo Wardani (Jurisprudensi: Jurnal Ilmu Syariah, Perundang-Undangan dan Ekonomi Islam, 2026)
Ideally, the protection of Indonesian Migrant Workers (IMWs), as mandated by the 1945 Constitution and Law Number 18 of 2017 on the Protection of Indonesian Migrant Workers (PPMI Law), positions the state as the primary human rights–based protector. In reality, persistent cases of violence, exploitation, human trafficking, and the failure of the zero-cost placement scheme reveal a significant gap caused by regulatory disharmony and overlapping institutional authority, particularly following the establishment of the Ministry of Indonesian Migrant Workers Protection (KP2MI). This study addresses the research gap (novelty) by examining the PPMI Law through a political law perspective that integrates human rights principles, institutional transformation of KP2MI–BP2MI, and comparative best practices from the Philippines. This research employs normative legal research using statutory, conceptual, and comparative approaches. The findings indicate that although the PPMI Law is normatively responsive, its implementation is weakened by the regulator–operator dilemma, inadequate supervision of private placement agencies, and limited responsiveness to emerging challenges such as online scamming and non-procedural migrant workers. This study recommends a revision of the PPMI Law to reaffirm institutional authority, strengthen substantive human rights protection, and adopt state-centered progressive protection models.